2005
DOI: 10.1152/jn.00458.2004
|View full text |Cite
|
Sign up to set email alerts
|

Background Synaptic Activity Modulates the Response of a Modeled Purkinje Cell to Paired Afferent Input

Abstract: Santamaria, Fidel and James M. Bower. Background synaptic activity modulates the response of a modeled Purkinje cell to paired afferent input. J Neurophysiol 93: [237][238][239][240][241][242][243][244][245][246][247][248][249][250] 2005. First published August 11, 2004; doi:10.1152/jn.00458.2004. We studied the possible effects of background excitatory and inhibitory synaptic activity on Purkinje cell responses to paired pulse inputs using a morphologically and physiologically detailed compartmental model. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 62 publications
3
40
0
Order By: Relevance
“…Alternative models, according to which parallel fibers adjust the response properties of the Purkinje-like AENs, have been suggested (Paulin, 2005;Paulin and Nelson, 1993;Paulin et al, 1998). These alternative models are consistent with experimental evidence (Bastian, 1986;Bower, 2002;Santamaria and Bower, 2005) about neuronal interactions in cerebellum and cerebellar-like sensory filtering structures.…”
Section: The Aff Input To the Donsupporting
confidence: 65%
“…Alternative models, according to which parallel fibers adjust the response properties of the Purkinje-like AENs, have been suggested (Paulin, 2005;Paulin and Nelson, 1993;Paulin et al, 1998). These alternative models are consistent with experimental evidence (Bastian, 1986;Bower, 2002;Santamaria and Bower, 2005) about neuronal interactions in cerebellum and cerebellar-like sensory filtering structures.…”
Section: The Aff Input To the Donsupporting
confidence: 65%
“…A previous in vitro study has shown that a single activation of ascending granule cell synapses can, in fact, produce prolonged intracellular plateau potentials in PCs (Jaeger and Bower 1994). Subsequent modeling studies (Santamaria and Bower 2005;Santamaria et al 2002) have suggested that these prolonged changes in PC activity are attributable to the long time constants of the calcium-related voltage-dependent conductances found in the dendrite and soma of PCs (Llinas and Sugimori 1980a,b). Interestingly, our models also suggest that the duration of these prolonged responses may be modulated by the rate of parallel fiber input to the PC dendrite (Santamaria and Bower 2005;Santamaria et al 2002).…”
Section: Variations In Relations Between the Gcl And Individual Pcsmentioning
confidence: 99%
“…However, these authors quantified evoked activity using an indirect voltage-sensitive dye measure in a slice preparation in which GABAergic inhibitory mechanisms were suppressed. We have recently shown that inhibition plays an important role in regulating the response of PCs to both ascending and parallel fiber granule cell inputs (Santamaria and Bower 2005;Santamaria et al 2002). In the absence of GABA inhibition, the slice preparation used by Vranesic et al (1994) in combination with direct electrical stimulation is likely to have artificially overwhelmed any effect of the ascending branch synapses.…”
Section: Excitatory Influence Of Ascending Segment Synapsesmentioning
confidence: 99%
See 2 more Smart Citations